Preparation method of wormlike nitrogen-doped carbon nanotube

The worm-like N-CNTs are prepared by calcining the COFs nanotubes as precursors in an inert atmosphere, which solves the high cost and harsh conditions of the existing N-CNTs preparation methods, and realizes an efficient and simple preparation process and Excellent physical and chemical properties.

CN119118114AActive Publication Date: 2024-12-13HENAN AGRICULTURAL UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411274946.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The existing preparation methods of nitrogen-doped carbon nanotubes (N-CNTs) rely on chemical deposition and template methods, and there are problems such as high cost of template agents, harsh preparation conditions, low sample yield, and limited nitrogen doping content. Its large-scale application.

Method used

The new layer-stacked covalent organic framework (COFs) nanotubes are used as precursors to prepare worm-like nitrogen-doped carbon nanotubes in one-step calcination under an inert atmosphere, avoiding the use of metal substrates and templates and simplifying the preparation process .

Benefits of technology

It has achieved worm-like N-CNTs with high yield, uniform morphology, large specific surface area, high nitrogen doping amount and stable structure. It has good electrolyte permeability and ion transport performance, and is suitable for energy storage and catalytic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118114A_ABST
    Figure CN119118114A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a wormlike nitrogen-doped carbon nanotube, which comprises the following steps of: firstly, preparing a high-yield covalent organic framework nanotube material (COFs) formed by stacking sheet layers by taking trimesic acid, trimesic acid and p-phenylenediamine as raw materials under the condition of adding a free radical oxidant; then, the covalent organic framework nanotube is used as a self-template, and the wormlike COFs-derived nitrogen-doped carbon nanotube is successfully prepared through carbonization treatment in an inert atmosphere. The method is simple and has certain universality, the nitrogen doping amount of the COFs-derived nitrogen-doped carbon nanotubes can be accurately controlled by regulating and controlling the calcination conditions, and the defect degree of the material is changed. The finally obtained wormlike COFs-derived nitrogen-doped carbon nanotube still keeps good tubular morphology and pore structure, has high specific surface area and nitrogen retention, and has potential application value in the fields of electrochemical energy storage, catalysis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon nanotube materials, and in particular relates to a method for preparing worm-shaped nitrogen-doped carbon nanotubes. Background Art

[0002] Nitrogen-doped carbon nanotubes (N-CNTs) are a new type of material that is produced by connecting or combining nitrogen atoms into a carbon skeleton through chemical bonds. The introduction of nitrogen atoms can provide more free electrons for conductivity on the one hand, and improve the wettability and acid-base properties of the material on the other hand, while increasing structural defects as the center of the catalytic reaction. Therefore, N-CNTs are widely used in lithium-ion batteries, supercapacitors, electrochemical catalysis and other fields.

[0003] However, the current preparation methods of N-CNTs rely more on chemical deposition and template methods, which have problems such as high template cost, harsh preparation conditions, low sample yield, and limited nitrogen doping content, which restrict the further application and development of large-scale N-CNTs. Therefore, there are still challenges in developing N-CNTs with low cost, mild conditions, simple operation, green and efficient, which is one of the problems that need to be solved urgently in the field of nitrogen-doped materials. In addition, studies have shown that the physical and chemical properties of N-CNTs are directly related to the number of layers, diameter and degree of defects of the nanotubes. Therefore, further fine-tuning the mesoscopic morphology and microstructure of N-CNTs is of great research significance to broaden the application of N-CNTs and promote its large-scale application.

[0004] Covalent organic frameworks (COFs) derived carbon materials are a new type of porous carbon materials with high specific surface area, rich functional groups and excellent physical and chemical properties, and have attracted much attention in recent years. By adjusting the structure and preparation conditions of COFs, the pore size, shape structure and surface functional groups of the derived carbon materials can be controlled, thereby achieving fine regulation of their physical and chemical properties. However, due to the current limitations of the morphology control and complex and harsh preparation conditions of covalent organic framework-derived carbon materials, the derived carbon materials often have problems such as uncontrollable morphology, low yield, and limited nitrogen doping. Summary of the invention

[0005] The present invention aims to provide a simple and efficient method, which is not limited by metal substrates and templates, and uses novel layer-by-layer stacked COFs nanotubes as precursors and calcinations under inert gas to prepare worm-like COFs-derived N-CNTs in one step.

[0006] Therefore, in a first aspect, the present invention provides a method for preparing worm-shaped nitrogen-doped carbon nanotubes, the method comprising: (1) dissolving trimesic acid and trimesic acid as morphology directing agents in 1,4-dioxane, subjecting them to ultrasonic treatment and stirring in sequence to obtain a colorless and transparent solution, and then adding a free radical oxidant and stirring to obtain a solution; (2) adding p-phenylenediamine to the above solution, subjecting it to ultrasonic treatment and stirring, to obtain a suspension; (3) adding acetic acid to the above suspension, heating and stirring to react, and after the reaction is completed, standing to obtain a precipitate, centrifuging the precipitate, washing it with a benign solvent, drying it in an oven, and refluxing the obtained powder in methanol to obtain a hollow COFs nanotube precursor; (4) placing the COFs nanotube precursor in a tube furnace and calcining it under an inert atmosphere to obtain worm-shaped nitrogen-doped carbon nanotubes.

[0007] In a preferred embodiment, in step (1), the free radical oxidant can be one of hydrogen peroxide and peracetic acid, with a concentration of 2-30%, preferably hydrogen peroxide with a concentration of 20%. The addition of the free radical oxidant can increase the tube forming rate of the product.

[0008] In a preferred embodiment, the mass ratio of trimesaldehyde: trimesic acid: free radical oxidant: phenylenediamine: acetic acid is 1: 0.1~2: 0.01~2: 0.2~4: 0.5~10; preferably, the mass ratio of trimesaldehyde: trimesic acid: free radical oxidant: phenylenediamine: acetic acid is 1: 0.5~1: 0.05~1: 1~3: 2~5.

[0009] In a preferred embodiment, in step (3), the benign solvent may be one or a mixture of tetrahydrofuran, methanol, and chloroform; preferably methanol.

[0010] In a preferred embodiment, in step (3), the stirring reaction temperature is 25 to 180 o C; reaction time is 0.5~72 h; standing time is 12~120 h.

[0011] In a preferred embodiment, in step (4), the calcination temperature is 400-900° C., preferably 600-800° C.; and the calcination time is 1-3 h, preferably 2 h.

[0012] In a preferred embodiment, in step (4), the inert atmosphere is nitrogen or argon, preferably argon.

[0013] In a second aspect, the present invention provides worm-shaped nitrogen-doped carbon nanotubes obtained by the above preparation method.

[0014] In a preferred embodiment, the worm-like nitrogen-doped carbon nanotube surface has regular curved wrinkles and hollow channels.

[0015] In a preferred embodiment, the pore size of the hollow channel is 5-50 nm, and the length is 100 nm-5 , the carbon wall is about 10~60 nm.

[0016] In a preferred embodiment, the nitrogen doping amount of the worm-shaped nitrogen-doped carbon nanotubes is 1.52-7.78 at %.

[0017] Technical Effects The present invention uses trimesic acid, p-phenylenediamine as raw materials, and prepares a high-yield COFs nanotube material formed by stacking sheets under the condition of adding a free radical oxidant. And using COFs nanotubes as self-templates, through a simple one-step calcination process, N-CNTs with uniform morphology and high specific surface area are prepared. The surface of the N-CNTs prepared by the present invention has regular curved wrinkles, and at the same time has a larger hollow channel inner diameter (5-50 nm), a smaller aspect ratio (length between 100nm and 50nm), and a smaller aspect ratio (length between 100nm and 50nm). , with an outer diameter of about 100 nm) and a thicker carbon wall (10-60 nm). These remarkable structural features are not only conducive to the penetration of electrolytes, rapid ion transport, exposure of N-doped active sites, etc., but also accelerate the mass transfer process related to energy storage and catalysis. By controlling the calcination temperature (400-900 o C), which can achieve two-dimensional fine adjustment of the defect degree of carbon atoms and the doping level of nitrogen atoms in N-CNTs. This method is not limited to metal substrates and templates, is easy to operate, and has high yield. The worm-like N-CNTs have the advantages of good hollow channels, low aspect ratio, and good structural stability. The preparation method of the present invention is simple and efficient. The synthesized worm-like nitrogen-doped carbon nanotube material still maintains the hollow structure of the original COFs, and has the advantages of large specific surface area, high nitrogen content (7.78 at%), and good structural stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of COFs-derived N-CNTs prepared in Example 1 of the present invention; Figure 2 The scanning electron microscope and transmission electron microscope images of the COFs nanotube precursor prepared by the present invention are compared with the product obtained without adding H2O2; Figure 3 The infrared spectra of COFs-derived N-CNTs prepared in the present invention at different heat treatment temperatures; Figure 4X-ray powder diffraction patterns of COFs-derived N-CNTs prepared in the present invention at different heat treatment temperatures; Figure 5 The scanning electron microscopy images of COFs-derived N-CNTs prepared in the present invention at different heat treatment temperatures; Figure 6 Raman spectra of COFs-derived N-CNTs prepared in the present invention at different heat treatment temperatures; Figure 7 The nitrogen adsorption-desorption curves of COFs-derived N-CNTs prepared in the present invention at different heat treatment temperatures; Figure 8 X-ray photoelectron spectra of COFs-derived N-CNTs prepared in the present invention at different heat treatment temperatures.

[0020] Specific embodiment In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0021] Embodiment 1: Weigh 100 mg of trimesic acid and 100 mg of trimesic acid, dissolve in 20 mL of 1,4-diepoxyhexane, and add 10 µL of 30% H2O2 solution; ultrasonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution; Then, 200 mg of p-phenylenediamine was added to the solution, ultrasonicated for 10 min, and stirred for 10 min to obtain a suspension with a precipitate; 0.2 mL of 3 mol / L acetic acid was added and stirred continuously at room temperature for 24 h. The green precipitate was sealed and stored for two days, then separated by centrifugation, washed with tetrahydrofuran and methanol reflux, and finally dried in an oven to obtain a COFs nanotube precursor with H2O2 added. The COFs nanotube precursor powder with an appropriate amount of H2O2 added was placed in a porcelain boat and transferred to a tube furnace. It was calcined at 500°C for 2 h in a nitrogen atmosphere with a heating rate of 2°C / min. Finally, COFs-derived N-CNTs with H2O2 added were obtained, which were worm-shaped nitrogen-doped carbon nanotubes.

[0022] Comparative Example 1: In order to highlight the effect of free radical oxidants on morphology regulation, the present invention further prepared COFs materials without adding hydrogen peroxide, and the preparation process is as follows: Weigh 100 mg of trimesic acid and 100 mg of trimesic acid, and dissolve them in 20 mL of 1,4-diepoxyhexanes. Ultrasonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution. Then, 200 mg of p-phenylenediamine was added to the solution, ultrasonicated for 10 min, and stirred for 10 min to obtain a suspension with a precipitate; 0.2 mL of 3 mol / L acetic acid was added and stirred continuously at room temperature for 24 h; the obtained green precipitate was sealed and stored for two days, then separated by centrifugation, washed with tetrahydrofuran and methanol reflux, and finally dried in an oven to obtain a COFs nanotube precursor without adding H2O2.

[0023] An appropriate amount of the COFs nanotube precursor powder without H2O2 added was placed in a porcelain boat and transferred to a tube furnace. It was calcined at 500°C for 2 h in a nitrogen atmosphere with a heating rate of 2°C / min to obtain COFs-derived N-CNTs without H2O2 added.

[0024] Embodiment 2: Weigh 100 mg of trimesic acid and 100 mg of trimesic acid, dissolve in 20 mL of 1,4-diepoxyhexane, and add 10 µL of 30% H2O2 solution; ultrasonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution; Then, 200 mg of p-phenylenediamine was added to the solution, ultrasonicated for 10 min, and stirred for 10 min to obtain a suspension with a precipitate; Add 0.2 mL of 3 mol / L acetic acid and stir continuously at room temperature for 24 h; the resulting green precipitate is sealed and stored for two days, then separated by centrifugation, washed with tetrahydrofuran and methanol reflux, and finally dried in an oven to obtain a stacked COFs nanotube precursor.

[0025] An appropriate amount of stacked COFs nanotube precursor powder was placed in a porcelain boat and transferred to a tube furnace. It was calcined at 400 °C for 3 h in a nitrogen atmosphere with a heating rate of 2 °C / min to obtain worm-like COFs-derived N-CNTs.

[0026] Embodiment 3: Weigh 100 mg of trimesic acid and 100 mg of trimesic acid, dissolve in 20 mL of 1,4-diepoxyhexane, and add 10 µL of 30% H2O2 solution; ultrasonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution; Then, 200 mg of p-phenylenediamine was added to the solution, ultrasonicated for 10 min, and stirred for 10 min to obtain a suspension with a precipitate; Add 0.2 mL of 3 mol / L acetic acid and stir continuously at room temperature for 24 h; the resulting green precipitate is sealed and stored for two days, then separated by centrifugation, washed with tetrahydrofuran and methanol reflux, and finally dried in an oven to obtain a stacked COFs nanotube precursor.

[0027] An appropriate amount of stacked COFs nanotube precursor powder was placed in a porcelain boat and transferred to a tube furnace. It was calcined at 600 °C for 2 h in an argon atmosphere with a heating rate of 2 °C / min to obtain worm-like COFs-derived N-CNTs.

[0028] Embodiment 4: Weigh 100 mg of trimesic acid and 100 mg of trimesic acid, dissolve in 20 mL of 1,4-diepoxyhexane, and add 10 µL of 30% H2O2 solution; ultrasonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution; Then, 200 mg of p-phenylenediamine was added to the solution, ultrasonicated for 10 min, and stirred for 10 min to obtain a suspension with a precipitate; Add 0.2 mL of 3 mol / L acetic acid and stir continuously at room temperature for 24 h; the resulting green precipitate is sealed and stored for two days, then separated by centrifugation, washed with tetrahydrofuran and methanol reflux, and finally dried in an oven to obtain a stacked COFs nanotube precursor.

[0029] An appropriate amount of stacked COFs nanotube precursor powder was placed in a porcelain boat and transferred to a tube furnace. It was calcined at 700 °C for 2 h in an argon atmosphere with a heating rate of 2 °C / min to obtain worm-like COFs-derived N-CNTs.

[0030] Embodiment 5: Weigh 100 mg of trimesic acid and 100 mg of trimesic acid, dissolve in 20 mL of 1,4-diepoxyhexane, and add 10 µL of 30% H2O2 solution; ultrasonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution; Then, 200 mg of p-phenylenediamine was added to the solution, ultrasonicated for 10 min, and stirred for 10 min to obtain a suspension with a precipitate; Add 0.2 mL of 3 mol / L acetic acid and stir continuously for 24 h; the obtained green precipitate is sealed and stored for two days, then separated by centrifugation, washed with tetrahydrofuran and methanol reflux, and finally dried in an oven to obtain a stacked COFs nanotube precursor.

[0031] An appropriate amount of stacked COFs nanotube precursor powder was placed in a porcelain boat and transferred to a tube furnace. It was calcined at 800 °C for 1 h in an argon atmosphere with a heating rate of 2 °C / min to obtain worm-like COFs-derived N-CNTs.

[0032] Embodiment 6: Weigh 100 mg of trimesic acid and 100 mg of trimesic acid, dissolve in 20 mL of 1,4-diepoxyhexane, and add 10 µL of 30% H2O2 solution; ultrasonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution; Then, 200 mg of p-phenylenediamine was added to the solution, and the mixture was stirred for 10 min to obtain a suspension with a precipitate; Add 0.2 mL of 3 mol / L acetic acid and stir continuously for 24 h; the obtained green precipitate is sealed and stored for two days, then separated by centrifugation, washed with tetrahydrofuran and methanol reflux, and finally dried in an oven to obtain a stacked COFs nanotube precursor.

[0033] An appropriate amount of stacked COFs nanotube precursor powder was placed in a porcelain boat and transferred to a tube furnace. It was calcined at 900 °C for 1 h in an argon atmosphere with a heating rate of 2 °C / min to obtain worm-like COFs-derived N-CNTs.

[0034] Performance Characterization The structure of the worm-like COFs-derived N-CNTs in the present invention is characterized in detail by infrared spectroscopy, X-ray powder diffraction, Raman spectroscopy and the like.

[0035] like Figure 2 As shown in the scanning electron microscope, after adding hydrogen peroxide as a free radical oxidant, the morphology of the COFs nanotube precursor changes from slender to short and thick, with a length of 100 nm~5 , with a diameter of about 100 nm. In addition, the tube formation rate of the overall sample was significantly improved, and the morphology was more uniform. At the same time, transmission electron microscopy showed that COFs nanotubes had a hollow channel structure of 5-50 nm and a thicker carbon wall (10-60 nm).

[0036] in addition, Figure 3 The infrared spectrum of the COFs precursor shows that with the increase of carbonization temperature, the characteristic peaks of the functional groups (such as 1616 cm -1 The vibrational contraction peak of the imine bond at 1158 cm -1 The CH bending vibration peak in the benzene ring at 240 nm gradually disappears, that is, COFs gradually transform from organic frameworks to inorganic carbon structures.

[0037] This can also be seen from Figure 4 The X-ray diffraction pattern of confirms that it exhibits a similar pattern. After carbonization, the characteristic diffraction peak originating from the (100) plane of COFs gradually disappears, and a characteristic broad peak appears at 23°, which is attributed to the (002) crystal plane of the carbon material.

[0038] Figure 1 and Figure 5 The scanning electron microscope images of COFs-derived N-CNTs at different calcination temperatures. Obviously, after high-temperature carbonization, the tubular morphology of COFs is still well maintained. This shows that the COFs tube has good structural stability, and the carbonization process does not damage the mesostructure of the tube. At the same time, it can be clearly seen that the surface of the nanotube presents regular curved wrinkles, that is, worm-like, which originates from the lamellar stacking structure of the COFs precursor. This wrinkled structure has a higher specific surface area and surface defects than traditional nanotubes with smooth surfaces. The results of the above infrared spectra, X-ray powder diffraction patterns and scanning electron microscope images fully prove that through a simple one-step carbonization process, the present invention transforms COFs nanotubes into worm-like N-CNTs.

[0039] Raman characterization can reflect the graphitization degree and defect degree of carbon materials. The present invention has carried out Raman tests on COFs-derived N-CNTs at different calcination temperatures, such as Figure 6 Among them, at 1335 cm -1 The relative intensity of the carbon D peak at 1580 cm -1 The G peak of carbon is used to characterize the sp2 structure. As the carbonization temperature increases, the ID / IG value gradually increases, indicating that the degree of defects in the carbon lattice in the material gradually increases. X-ray photoelectron spectroscopy can analyze the nitrogen content in COFs-derived N-CNTs. The results are as follows Figure 7 And as shown in Table 1.

[0040] Table 1 It can be seen that after carbonization, the nitrogen content in COFs-derived N-CNTs can be controlled in the range of 1.52~7.78 at%. Specifically, before 500°C, as the carbonization temperature continues to increase, the nitrogen content in N-CNTs gradually increases. On the one hand, this is due to the in-situ doping of nitrogen atoms in COFs in the carbon layer. On the other hand, the higher the temperature, the easier it is for the functional groups to be lost in the form of small gas molecules. After 500°C, the continued increase in temperature causes the nitrogen content to gradually decrease. This is because the degree of graphitization of the carbon structure increases, causing the N atoms to be squeezed out of the carbon lattice. Combining Raman spectroscopy and X-ray photoelectron spectroscopy, it can be proved that by controlling the carbonization temperature, the dual regulation of the defect degree and nitrogen doping level of COFs-derived N-CNTs can be achieved, that is, the nitrogen doping level can be precisely controlled. In addition, COFs-derived N-CNTs also have a high specific surface area, such as Figure 8 And as shown in Table 2.

[0041] Table 2 Nitrogen adsorption and desorption experiments show that with the continuous increase of carbonization temperature, the specific surface area of ​​N-CNTs gradually increases, and the specific surface area reaches the maximum at 600°C. However, as the carbonization temperature continues to increase, the specific surface area decreases, which may be caused by the breakage of CN bonds and the collapse of pore structure due to excessively high temperature.

[0042] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing worm-shaped nitrogen-doped carbon nanotubes, the method comprising: (1) dissolving trimesic acid and trimesic acid as morphology directing agents in 1,4-dioxane, subjecting them to ultrasonic treatment and stirring in sequence to obtain a colorless and transparent solution, and then adding a free radical oxidant and stirring to obtain a solution; (2) adding p-phenylenediamine to the above solution, subjecting it to ultrasonic treatment and stirring, to obtain a suspension; (3) adding acetic acid to the above suspension, heating and stirring, and standing after the reaction is completed to obtain a precipitate, centrifuging the precipitate, washing it with a benign solvent, and drying it in an oven. The obtained powder is refluxed in methanol to obtain a hollow COFs nanotube precursor; (4) placing the obtained COFs nanotube precursor in a tube furnace and calcining it under an inert atmosphere to obtain the worm-like nitrogen-doped carbon nanotubes.

2. The preparation method according to claim 1, wherein In step (1), the free radical oxidant is one of hydrogen peroxide and peracetic acid, and the concentration is 2-30%.

3. The preparation method according to claim 1, wherein The mass ratio of trimesaldehyde: trimesic acid: free radical oxidant: phenylenediamine: acetic acid is 1:0.1~2:0.01~2:0.2~4:0.5~10.

4. The preparation method according to claim 1, wherein In step (3), the benign solvent is one or a mixture of tetrahydrofuran, methanol, and chloroform.

5. The preparation method according to claim 1, wherein In step (3), the stirring reaction temperature is 25~180oC; the reaction time is 0.5~72 h; and the standing time is 12~120 h.

6. The preparation method according to claim 1, wherein In step (4), the calcination temperature is 400-900°C.

7. The preparation method according to claim 1, wherein In step (4), the calcination time is 1 to 3 h.

8. The preparation method according to claim 1, wherein In step (4), the inert atmosphere is nitrogen or argon.

9. The worm-shaped nitrogen-doped carbon nanotube obtained by the preparation method according to any one of claims 1 to 8.

10. The worm-shaped nitrogen-doped carbon nanotube according to claim 9, wherein: Its surface has regular curved wrinkles and hollow channels, the pore size of which is 5-50 nm and the length is 100 nm-5 , the carbon wall is 10~60nm.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped carbon nanotubes

    CN105355934A

  • Carbon nanotube material derived from covalent organic framework and preparation method of carbon nanotube material

    CN111977638A

  • Covalent organic framework nanotube material and preparation method thereof

    CN114874451A

  • Three dimensional COF-graphene and COF-CNT hybrids with remarkable chemical stability for methane storage

    WO2022038627A1

  • AU2020101584A4